Simulation of Alumina/Water Nanofluid Flow in a Micro-Heatsink With Wavy Microchannels: Impact of Two-Phase and Single-Phase Nanofluid Models - Khetib, Yacine; Abo-Dief, Hala M.; Alanazi, Abdullah K.; Saleem, Hussein A.; Sajadi, S. Mohammad; Sharifpur, Mohsen (Frontiers in Energy Research, 2021)
In this paper, alumina/water nanofluid (NF) flow in a heatsink (H-S) with wavy microchannels (W-MCs) is simulated. The H-S is made of aluminum containing four similar parts. Each part has an inlet and outlet. Constant heat flux is applied on the bottom of the H-S. The study is based on two-phase mixture (T-P) and single-phase (S-P) models to determine the difference between these two types of simulation. FLUENT software is used for the simulations. The volume control method is employed to solve the equations. The effective variables include the volume fraction 0 < φ < 5% of alumina and Reynolds number (Re) 300 < Re < 1800. The maximum H-S bottom temperature, the amount of required pumping power (PP), the temperature uniformity, and the heat resistance of the H-S are the outputs studied to simulate S-P and T-P models. The results show that the use of the T-P model has less error in comparison with experimental data than the S-P model. An increment in the Re and φ reduces the maximum temperature of the H-S. The S-P model, especially at a higher value of φ, leads to a lower maximum temperature (M-T) value than the T-P model. Temperature uniformity is improved with Re and φ. The reduction of H-S thermal resistance with Re and φ is the result of this study. Adding nanoparticles (NPs) to water, especially at higher amounts of φ, enhances the required PP. The T-P model predicts higher PP than the S-P one, especially at a high value of φ.